Violations of the right to access information—takeover of public media - Wąsowski, Krzysztof (Finding a way out of Poland's rule-of-law crisis: Possible courses of action and reform, 2026)
On December 19, 2023, the Minister of Culture, Bartłomiej Sienkiewicz, appointed new supervisory boards for Telewizja Polska, Polskie Radio, and the Polish Press Agency based on the Commercial Companies Code, completely disregarding the provisions of the Broadcasting Act. The following day, the new management took over the media by force, suspending the broadcast of some channels. On December 27, the minister announced the placement of the companies into liquidation.The Constitutional Tribunal had already prohibited such actions in an interim order on December 14, 2023, and confirmed their unconstitutionality in a ruling on January 18, 2024. The entries of the liquidators in the National Court Register (KRS) should be considered legally ineffective. Those responsible for shutting off the stations' signal should bear compensatory and criminal liability, and the Minister of Justice should request the initiation of disciplinary proceedings against the notary who drew up the minutes of the general meetings.The author advocates for restoring the participation of the National Broadcasting Council (KRRiT) in the procedure for appointing the authorities of public media as the only solution to remove doubts regarding the legality of this process.